EVOLUTION OF PRIVATIZATION AND DEPUTY OF STATE IN THE INDUSTRIAL SECTOR OF UZBEKISTAN (World Economics and Finance Bulletin, 2023)
In the article, the author pays special attention to the features of privatization, denationalization and, on the basis of this, to create multi-structural ownership, privatization models, and the formation of a market economy